Analisis Financial Literation, Financial Technology, Locus of Control Terhadap Financial Behavior - Hikmah, Hikmah; Azmiana, Risca; Haldy, Muhammad (LPPM Universitas Putera Batam, 2024)
Various new and diverse financial products require people to understand them more deeply if they want to use them. This is necessary to avoid making bad financial decisions, or, in other words, bad financial behavior. Individual finances can be managed well if the individual's financial behavior is responsible. Financial behavior is one of the issues that is widely discussed today. This has an impact on many phenomena that arise in Indonesian society related to poor financial management. This research is a quantitative study that aims to determine the influence of financial literacy, financial technology, and locus of control on financial behavior. The population in this study were students in Batam City. The sample size was taken as 115 respondents, using non-probability sampling and purposive sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (partial least squares) analysis method with SmartPLS 4.0 software. The results of this study show that (1) financial literacy has a significant positive influence on financial behavior. (2) Financial technology has no significant influence on financial behavior. (3) Locus of control does not influence financial behavior.